Student Perceptions of Using Prezi Media in General Indonesian Courses - Ayu Gustia Ningsih; Vivi Indriyani; Aditya Rachman (AL-ISHLAH: Jurnal Pendidikan, 2023)
Numerous facets of life, especially the field of education, have been significantly impacted by the COVID-19 epidemic. The switch from traditional classroom instruction to online or virtual instruction can be challenging for both instructors and students. In an effort to achieve the best learning objectives, Prezi media is one of the online learning methods and resources that are chosen and employed. It is widely used during presentations and group discussions. The study's goal was to ascertain how the Prezi content utilized in general Indonesian classes was perceived by the students. This qualitative study included 50 students in total as research participants. The information was gathered through the use of a Likert scale questionnaire, and it was then reviewed in three stages: data reduction, data presentation, and conclusion-making. The study's findings suggest that using Prezi media to support students in meeting their learning objectives has considerable advantages. These advantages consist of how simple it is to comprehend the subject matter, how efficient studying time is, and how appealing and how practical it is.